HUBUNGAN ANTARA POLA ASUH ORANG TUA DENGAN KECERDASAN EMOSIONAL SISWA - Novita, Lina (Program Pendidikan Guru Sekolah Dasar Universitas Pakuan, 2018)
The purpose of this study is to determine the relationship between parenting towards students’ eemotional intelligence. The researsh applies survey method with correlation approach. The data are obtained from the population sample of Pondok Rumput elementary school, Bogor. The result of the trial shows that parenting variable consisting of 50 items tested have 37 valid items, 13 items are not valid with realibility coefficient of 0.781. Meanwhile, emotional intelligence variable consisting of 50 items tested have 35 valid items, and 15 items are not valid with realibility coefficient of 0.804. The result of the study shows that there is correlation between emotional intelligent towards parenting based on the statistical analysis. Hence, one of the efforts to develop the students’ emotional intelligence is by improving parental care.Keywords: parenting, emotional intelligence.